2023
DOI: 10.1017/wsc.2023.46
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cereal rye cover crop on the fate of preemergence herbicides flumioxazin and pyroxasulfone and control of Amaranthus spp. in soybean

Jose Nunes,
Nicholas J. Arneson,
John Wallace
et al.

Abstract: Preemergence herbicides associated with cereal rye (Secale cereale L.) cover crop (cereal rye) can be an effective waterhemp [Amaranthus tuberculatus (Moq.) Sauer.] and Palmer amaranth (Amaranthus palmeri S. Watson) management strategy in soybean [Glycine max (L.) Merr.] production. Delaying cereal rye termination until soybean planting (planting green) optimizes biomass production and weed suppression but might further impact the fate of preemergence herbicides. Limited research is available on the fate of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It is important to emphasize that this study focused on the physical influence of the cereal rye biomass on A. tuberculatus suppression and soil microenvironment (light, moisture, and temperature). The methodology adopted simulates the mulch effect of the cereal rye biomass following its termination and during decomposition, which is commonly observed when cereal rye is adopted ahead of soybean (Nunes et al 2023b). Because there was no cereal rye growth in the experimental area where the study was conducted, this study did not account for the effect of the cover crop on water (Reed and Karsten 2022) and nutrient (Finney et al 2016) dynamics during its growth and their potential impact on A. tuberculatus recruitment (Boyd and Van Acker 2003;Sweeney et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to emphasize that this study focused on the physical influence of the cereal rye biomass on A. tuberculatus suppression and soil microenvironment (light, moisture, and temperature). The methodology adopted simulates the mulch effect of the cereal rye biomass following its termination and during decomposition, which is commonly observed when cereal rye is adopted ahead of soybean (Nunes et al 2023b). Because there was no cereal rye growth in the experimental area where the study was conducted, this study did not account for the effect of the cover crop on water (Reed and Karsten 2022) and nutrient (Finney et al 2016) dynamics during its growth and their potential impact on A. tuberculatus recruitment (Boyd and Van Acker 2003;Sweeney et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Yadav et al (2023) reported that cereal rye associated with reduced soybean row spacing (38 vs. 76 cm) and effective A. tuberculatus control in the previous crop (corn) provided the best level of A. tuberculatus control during the soybean season. Nunes et al (2023b) observed that a cereal rye cover crop terminated at soybean planting (planting green) reduced early-season A. tuberculatus density similar to the use of a preemergence herbicide program. These studies provide evidence that cereal rye can be an effective tool for A. tuberculatus management.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, FLU has also been widely used in integrated weed management in no-till fields and orchards. 16,17 This constraint underscores the need for novel PPO inhibitors with enhanced selectivity and efficiency. 8,9,18 In 2003, Hamprecht et al employed a substructure splicing strategy to synthesize a biphenyl compound (Figure 1) with weak herbicidal activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, because of its limitation in crop selectivity, FLU has only been used as a pre-emergence herbicide in crop fields such as cotton, peanut, and soybean. In addition, FLU has also been widely used in integrated weed management in no-till fields and orchards. , This constraint underscores the need for novel PPO inhibitors with enhanced selectivity and efficiency. ,, …”
Section: Introductionmentioning
confidence: 99%